The Terrible Two - Barnett, Mac 1982-; John, Jory (Amulet Books, 2015)
When master prankster Miles Murphy moves to sleepy Yawnee Valley, he challenges the local, mystery prankster in an epic battle of tricks but soon the two join forces to pull off the biggest prank ever seen
Keywords: Practical jokes; Tricks; Schools; Moving, Household; Humorous stories; Jugendbuch; Kinderbuch